Pengaruh Penguasaan Teknologi Informasi, Efikasi Diri, dan Keterampilan Komunikasi Interpersonal terhadap Kesiapan Kerja Mahasiswa Generasi Z - Octhaviana, Yaula; Rahmaningtyas, Wisudani (Jurnal Simki Pedagogia, 2025)
In an era of increasingly competitive job competition, work readiness is not only technical skills but also the mental, social, and digital readiness of graduates. However, there are still many students who show that their mastery of information technology has not been fully utilized to support the development of work competencies. Low self-efficacy and lack of interpersonal communication skills are quite significant obstacles. This study was conducted to examine the effect of mastery of information technology, self-efficacy, and interpersonal communication skills on the work readiness of generation Z students of the Economic Education Study Program (Office Administration) class of 2021, Semarang State University. The quantitative research approach is descriptive. The population in this study includes all generation Z students of the Economic Education Study Program (Office Administration) class of 2021, Semarang State University, totaling 131 students. Sample selection was carried out using a saturated sampling approach by involving the entire population in the study. Data collection techniques used questionnaires and documentation. The data analysis technique applied descriptive analysis and multiple regression analysis using the assistance of the IBM SPSS Statistics 26 for Windows program. The results of the study indicate that there is an influence between mastery of information technology, self-efficacy, and interpersonal communication on the work readiness of generation Z students of the Economic Education Study Program (Office Administration) Semarang State University.